Unit Iii Laplace Transform
Unit Iii Laplace Transform
Unit Iii Laplace Transform
LAPLACE TRANSFORM
DR. ABDUL HAQ
DEPARTMENT OF MATHEMATICS,
COLLEGE OF ENGINEERING AND
TECHNOLOGY,
SRM INSTITUTE OF SCIENCE AND
TECHNOLOGY,
KATTANKULATHUR
INTRODUCTION
• BASIC DEFINITIONS
• TRANSFORMS OF SIMPLE FUNCTIONS
• BASIC OPERATIONAL PROPERTIES
• TRANSFORMS OF DERIVATIVES AND INTEGRALS
• INITIAL AND FINAL VALUE THEOREMS
• LAPLACE TRANSFORM OF PERIODIC FUNCTIONS
• INVERSE TRANSFORMS
• CONVOLUTION THEOREM
• APPLICATIONS OF LAPLACE TRANSFORMS FOR SOLVING FIRST AND
SECOND ORDER LINEAR ORDINARY DIFFERENTIAL EQUATION
INITIAL VALUE THEOREM
If 𝐿 𝑓 𝑡 = 𝐹(𝑠) then 𝑙𝑖𝑚𝑡→0 𝑓 𝑡 = 𝑙𝑖𝑚𝑠→∞ 𝑠𝐹 𝑆 , provided the limits
exist.
Proof: WKT
𝐿 𝑓′ 𝑡 = 𝑠𝐿 𝑓 𝑡 − 𝑓 0 = 𝑠𝐹 𝑠 − 𝑓 0
Therefore
𝑙𝑖𝑚𝑠→∞ 𝐿 𝑓 ′ 𝑡 = 𝑙𝑖𝑚𝑠→∞ 𝑠𝐹 𝑠 − 𝑓 0
∞
= 𝑙𝑖𝑚𝑠→∞ 𝑒 −𝑠𝑡 𝑓 ′ 𝑡 𝑑𝑡 = 0
0
∴ 𝑙𝑖𝑚𝑠→∞ 𝑠𝐹 𝑠 = 𝑓 0 = 𝑙𝑖𝑚𝑡→0 𝑓 𝑡 .
FINAL VALUE THEOREM
If 𝐿 𝑓 𝑡 = 𝐹(𝑠) then 𝑙𝑖𝑚𝑡→∞ 𝑓 𝑡 = 𝑙𝑖𝑚𝑠→0 𝑠𝐹 𝑆 , provided the limits
exist.
Proof: WKT
𝐿 𝑓′ 𝑡 = 𝑠𝐿 𝑓 𝑡 − 𝑓 0 = 𝑠𝐹 𝑠 − 𝑓 0
Therefore
∞
𝑙𝑖𝑚𝑠→0 𝑠𝐹 𝑠 − 𝑓 0 = 𝑙𝑖𝑚𝑠→0 𝑒 −𝑠𝑡 𝑓 ′ 𝑡 𝑑𝑡 = 0
0
∞
= 𝑓 ′ 𝑡 𝑑𝑡 = [𝑓 𝑡 ]∞
0
0
= 𝑙𝑖𝑚𝑡→∞ 𝑓 𝑡 − 𝑓(0)
∴ 𝑙𝑖𝑚𝑡→∞ 𝑓 𝑡 = 𝑙𝑖𝑚𝑠→0 𝑠𝐹 𝑆 .
PERIODIC FUNCTIONS
∞
𝐿 𝑓 𝑡 = 𝑒 −𝑠𝑡 𝑓 𝑡 𝑑𝑡
0
𝑇 2𝑇 3𝑇
= 𝑒 −𝑠𝑡 𝑓 𝑡 𝑑𝑡 + 𝑒 −𝑠𝑡 𝑓 𝑡 𝑑𝑡 + 𝑒 −𝑠𝑡 𝑓 𝑡 𝑑𝑡 + ⋯
0 𝑇 2𝑇
T
sT su
e e f (u ) du, ( f (u T ) f (u ))
0
u t 2T
dt du
3T u T s (u 2T )
e st f (t )dt e f (u 2T ) f (u 2T )du
2T u0
T
e 2 sT su f (u )du, ( f (u 2T ) f (u ))
e
0
T T
L{ f (t )} e su f (u )du e sT su f (u )du
e
0 0
T
2 sT su f (u )du ....
e e
0
T
L{ f (t )} (1 e sT e 2 sT ....) e su f (u )du
0
T
sT 1
(1 e ) e su f (u )du, ( (1 x) 1 1 x x 2 ...)
0
T
e su f (u )du
1
1 e sT 0
T
e sT f (t )dt
1
L{ f (t )}
1 e sT 0
PROBLEMS
1) Find the Laplace Transform of the rec tan gular wave for the given
function,
1, 0 t b
f (t )
1, b t 2b
Solution:
1 T
WKT L{f(t)} e st f(t)dt, 0tT
1 e sT 0
Here T 2b
2b
e st f (t ) dt
1
L{ f (t )}
1 e 2bs 0
1
b st 2b
st ( 1) dt
e (1) dt e
1 e 2bs
0 b
st
b
st
2b
1 e
e
1 e 2 bs s s
0 b
1 e bs 1 e 2bs e bs
L f t
1 e 2bs s s s s
1 2bs
2e bs 1
1
e
1 e 2bs s
2
1 1
L f t 1 e bs
1 e 2bs s
2
1 e bs
1 1
L f t
1 e bs 1 e bs s
1 e bs
s 1 e bs
bs bs
1e 2 e 2 1 bs
L f t tan h
s bs
bs s 2
e 2 e 2
PROBLEM 2 :
Find the laplace transform of the function
t, 0t
f (t )
2 t , t 2
where f (t 2 ) f (t )
SOLUTION:
1 T
WKT L{f(t)} sT
e sT f(t)dt, 0tT
1 e 0
where T 2
1 st 2
L{ f (t )} te dt 2 t e st
dt
1 e 2s 0
2
1 e st e
st
e st
e
st
t 1 2 2 t 1 2
1 e 2s s s 0 s s 0
1 e s e s 1 s e 2 s e s
2s
2 2 e 2 2
1 e s s s s s s
1 1 s
2 s
2 s 2
1 2 e e
1 e s
1 e
s
2
1 e s 2
s 1 e
2
s 1 e 1 e
2s 2 s s
L f t
1 e
s
s 1 e
2 s
s2
s
1 e e 2
2 s s
s 2
e e
2
1 s
L f t tanh
s2 2
PROBLEM 3 :
Find the Laplace Transform of the periodic function given by
sin t , 0 t
f (t )
0, 2
t
2
and its period is .
SOLUTION:
1 T
WKT Lf t sT e st
f(t)dt, 0tT
1 e 0
2
where T
2
L f (t )
1
e
st
s 2
f (t )dt
1 e
0
2
1 st
e sin t e 0 dt
st
s 2
1 e
0
e st
1
2 s sin t cos t
1 e 2 s s 2
0
1 e s 1
L f t s2 2 cos cos 0
1 e 2 s s2 2
1
. 1 e s
1 e 2 s s
2 2
1
L f t
s 2 2 1 e s
TASK :
1) Find the Laplace Transform of the function
t for 0 t
f (t )
t for t 2
IMPORTANT RESULTS
1) L1{1 /(s a )} e at
2) L1{1 /(s a )} e at
6) L1{a /( s 2 a 2 )} sinh at
7) L1{1 / s} 1
8) L1{1 / s 2 } t
9) L1{1 /( s 2 a 2 )} te at
respectively , then
PROBLEM 1
1 1 s
Find L1 2
s 3 s s 4
Solution :
1 1 s 1 1 1 1 1 s
L1 2 L L L 2 2
s 3 s s 4 s 3 s s 2
e 3t 1 cosh2t
PROBLEM 2
1 1 1 s
Find L1 2 2 2
s s 4 s 4 s 9
Solution :
1 1 1 s
L1 2 2 2
s s 4 s 4 s 9
1 1 1 1 1 s
L1 2 L1 L 2 L 2 2
s s 4 s 4 s 3
1 1 1 1 2 1 s
L1 2 L1 L 2 2 L 2 2
s s 4 2 s 2 s 3
1
t e 4t sin2t cosh3t
2
FIRST SHIFTING PROPERTY :
If L f t F s , then L e at f t F s a .
Hence L1 F s a e at f t
PROBLEM 1
1
Find L1 2
s 1
Solution :
1 t 1 1
L1 e L 2 e t t
s 1 s
2
s 3
PROBLEM 2 : Find L1
s 3 4
2
Solution :
s 3 3t 1 s
L1 e L 2 2
e 3t cos2t
s 3 4 s 2
2
s
PROBLEM 3 : Find L1 2
s b a
2
Solution :
s 1 s bb
L1 L 2
s b a s b a
2 2 2
s 1 s b 1 b
L1 L L 2
s b a s b a s b a
2 2 2 2 2
s b a
ebt L1 2 2 ebt L1 2 2
s a a s a
s b bt
L1 e bt
cos at e sin at.
s b a
2 2
a
RESULT 1 : L1Fs t L1Fs
s
PROBLEM 1 Find 1
L 2
s a
2 2
Solution :
F s
s
s 2
a2
2
F s
s
s 2
a2 2
ds
Put s 2
a2 t
2 sds dt
s dt
s 2
a
2 2
ds 2t 2
1 1 1 1
2
2 t 2 s a 2
s 1
s 2
a
2 2
ds
2 s a2
2
1
t L1 2
2 s a
2
1 s t 1 1
L 2
L 2 2
s 2 a 2 2 s a
t 1 1 a
. L 2 2
2 a
s a
1 s t
L 2
sinat
s 2 a 2 2a
s3
PROBLEM 2 Find L1
s 6 s 13
2
2
Solution :
s3
F s
s 2
6 s 13 2
F s
s 3ds
s 2
6 s 13
2
Put s 2 6 s 13 t
2 s 6 ds dt
s 3ds dt
2
s 3ds dt 1 1
s 2
6 s 13
2
2t 2 2 t
s 3ds 1 1
s 2
6 s 13
2
2 s 2 6 s 13
WKT L1 F1 s t L1Fs
1
t L1
2 s 6 s 13
2
t 1 1
L 2
2
s 6 s 13
t 1 1
L
s 3 4
2
2
t 3t 1 1 2
e L 2 2
2 2 s 2
t 3t
e sin 2t
4
d 1
RESULT 2 : L1 s Fs L Fs
dt
s
PROBLEM 1 Find L1
s 2 2
4
Solution :
F s
s
s 22 4
d 1
WKT L1 s Fs L Fs
dt
1 d 1 1
L1 s. L
s 2 2
4 dt s 2 2
4
d 2t 1 1
e L 2 2
dt s 2
d 2t 1 1 2
e L 2 2
dt 2 s 2
d 2t 1
e sin 2t
dt 2
1 d 2t
2 dt
e sin 2t
1 2t
2
e 2 cos 2t sin 2t. 2e 2t
e cos 2t sin 2t
s
L1 2t
s 2 4
2
s2
PROBLEM 2 Find L 1
2
s 2 a 2
Solution :
1 s2
1 s
L L s. 2
s 2 a 2
2
s 2 a 2
L1s. F s
where F s
s
s 2
a2
2
d 1
WKT L1s Fs L Fs
dt
d 1
.............................1
s
L 2
dt s 2 a 2
s
Consider L1 2
s 2 a 2
F 1 s
s
s 2
a2 2
s
F s ds
s 2
a 2
2
Put s 2
a 2 t
dt
2 s ds dt s ds
2
s dt
ds
s 2
a2
2
2t2
1 1
2 t
1 1
2
2 s a2
WKT L1 Fs t L1 Fs
1
t L1 2 2
2 s a
t 1 1
L
2 s2 a2
t 1 a
. L1 2 2
2 a s a
sin at........................................2
t
2a
substituti ng 2 in 1,
1 s2 d t
L 2
sin at
s 2 a 2 dt 2a
1 d
t sin at
2a dt
1
a t cosat sinat
2a
Fs
t
RESULT 3 L1 L1 Fs dt
s 0
1
PROBLEM 1 Find L1 2
s s a
2
Solution :
Fs
t
WKT L1 L1 Fs dt
s 0
Fs
1
s a2
2
1 1 1
t
L1 . 2 L
1
2
2 2
dt
s s a 0 s a
a
t
1
L
1
2 2
dt
a 0 s a
t
1
sin at dt
a0
t
1 cos at
a a 0
2 1 cos at
1 1
L1 2 2
s s a a
1
PROBLEM 2 Find L1 2
s s a
Solution :
Fs
t
WKT L1 L1Fs dt
s 0
1 1 1 1
L1 2 L .
s s a s s s a
where F s
1
s s a
1 1 1 1
t
L1 . L
dt ...................................1
s s a 0 s s a
1 t 1 1
L
1
L dt
s s a 0 s a
t
e at dt
0
t
e at
a 0
1 e at .................................2
1
a
substitute 2 in 1,
1
1 t
1
L 2 1 e at dt
s s a 0
a
1 e dt
t
1 at
a 0
1
t
t e
at
t 0
a a 0
1 1 1 e at 1
L 2 t
s s a a a a
1
PROBLEM 3 : Find L1 2
s s 2s 5
Solution:
Fs
t
L Fs dt
1 1
WKT L
s 0
1 t 1 1
L 2
1
L 2 dt
s s 2s 5 0 s 2s 5
t
1
L1 2 dt
0 s 2 s 1 5 1
t
1
L1 2
dt
0 s 12
2
1
t
e t L1 2 2
dt
0 s 2
1 t
t 1 1 2
1
L 2
s s 2
2 s 5 0
e
2
L
s 2
2
dt
t
1
e
t
sin 2t dt
2 0
e ax
WKT e
ax
sinbx dx 2 asinbx bcosbx
a b2
t
1 et
sin 2t 2 cos 2t
25 0
1 1
L1 2
e t sin 2t 2 cos2t 2
s s 2s 5 10
s b
PROBLEM 1 : Find L1 log
s a
Solut ion :
sb
Let F s log
sa
F s logs b logs a
F s
1 1
sb sa
s b
L1 log
1
e bt e at
s a t
1 s b e at e bt
L log
sa t
s 2 a 2
PROBLEM 2 : Evaluate L log
s2 b2
1
Solut ion :
1 1 '
WKT L1Fs
t
L F s
s2 a2
Let F s log 2
2
s b
log s 2 a 2 log s 2 b 2
F s
2s 2s
s2 a2 s 2 b2
s2 a2 2
1
L log 2 2
cos bt cos at
s b t
TASK :
s
1 Find L1 2
s 2
1
2 Find L1
5
s 3
2
s 4 s 2 5 s 3 6
5 2 2 2
2s 3 1
3 Find L 1
18
s 2
2s 1
4 Find L1 2
s 2s 2
2
5 Find L1
1
s s 3
s2
6 Find L1 2
s 2 2
1 s
7 Find L1 log 2
s
2
8 Find L log
1
1 2
s
RESULT 4 : L1{e as F s } f t a H t a
f t t t a H t a
a s
F s tan 1 cot1
s b
Solution:
a s
F s tan 1 cot1
s b
1 a 1 1
F s 2
1 2
s
1 2
a 2 2
s b
s b
a b
F s 2
d
ds s a
2
s 2 b 2
d
WKT L{t f t } Fs
ds
a b
L{tf (t )} 2
s a
2
s 2 b 2
t f t sin at sin bt
f t
1
sin at sin bt
t
L1 {F ( s )}
1
sin at sin bt
t
a s 1
L1 tan1 cot 1 sin at sinbt
s b t
PROBLEM 2 : If L f t e 3 s tan 1 s . Find f 0 .
Solution :
Given L{ f (t )} e 3 s tan 1 s
Let L1{tan 1 s } g t
L{g (t )} tan 1 s
G s tan 1 s
G s
d
WKT L{tg (t )}
ds
d
L{g (t )}
ds
d
ds
tan 1 s
1
L{tg (t )} 2
1 s
1
t g t L1 2
1 s
sin t
g t
sin t
t
L1 tan 1 s
sin t
t
1 f t sin t H t 3
t t t 3
sin t 3
H t 3
t 3
sin t 3
,t 3
f t t 3
0 , t 3
f 0 0
METHOD OF PARTIAL FRACTIONS :
fn A B
TYPE I :
s s a s s a
fn A Bs C
TYPE II :
s s 2 2as a 2 s s 2 2as a 2
fn A B C
TYPE III :
s a 3 s a s a 2 s a 3
fn As B Cs D Es F
TYPE IV :
s 2
a 2 s 2 b 2
2
s 2 a 2 s 2 a 2 2 s 2 b 2
1
PROBLEM 1 : Find L1
s s 1s 2
Solution :
F s
1
s s 1s 2
1 A s 1s 2 B s s 2 C s s 1
s s 1s 2 s s 1s 2
1 A s 1s 2 B s s 2 C s s 1
1 1
A ; B 1; C
2 2
Substitute the values of A, B and C in 1,
1
1 2 1 1 2
s s 1s 2 s s 1 s 2
1 1 2t
1 e
1
L1 t
e
s s 1 s 2 2 2
1 s
Find L1
PROBLEM 2 :
s 1 s
2
4 s 13
Solution :
1 s
F s
s 1 s 2 4s 13
1 s A Bs C
.....................1
s 1s 4s 13 s 1 s 4s 13
2 2
1 8
s
1 s
2
1 5 5
s 1s 4s 13 5s 1 s 4s 13
2
1 s 8
5s 1 5s 2 4 s 13 5s 2 4 s 13
1 s 8
5s 1
5 s 2 9
2
5 s 2 9
2
Taking L1 on both sides,
1 s 1 1 1 1 1 s
L1
s 1s 2
4 s 13
5
L
s 1
5
L
s 2 2
9
8 1 1
5
L
2
s 2 9
1 s 1 t 1 1 s 2 2 8 1
L1 2
1
2
s 1 s 4 s 13 5
2
e L
5 s 2 3 5
2
L
s 2 3
2
1 1 1 s 2 1 1 8 1 1
e t
L 2 L 2
L 2
5 5 s 2 2 32 s 2 3 5 s 2 3
2 2
1 1 s 1 8 1
e t e 2t L1 2 2 2 e 2t L1 2 2 e 2t L1 2 2
5 5 s 3 s 3 5 s 3
1 s
L1
s 1
s 2
4 s
13
1 t 1 2t 1 s 2 e 2t 1 3 8 e 2t 1 3
e e L 2 2 L 2 2 L 2 2
5 5 s 3 5 3 s 3 5 3 s 3
1 1 2 2t 8
e t e 2t cos 3t e sin 3t e 2t sin 3t
5 5 15 15
1 s 1 t 1 2t 3 2t
L1 e e cos 3t e sin3t
s 1 s 4s 13
2
5 5 5
5s 2 15s 11
1
PROBLEM 3 : Find L 3
s 1s 2
Solution :
5s 2 15s 11
F s
s 1s 23
5s 2 15s 11
.......... .....1
A B C D
s 1s 23 s 1 s 2 s 22 s 23
1 1
A ; B ; C 4; D 7
3 3
1 1 1 1
e t e 2t 4 e 2t L1 2 7e 2t L1 3
3 3 s s
5s 2 15s 11
1 1 t 1 2t 2t 2t t
2
L 3
e e 4 e .t 7e
s 1s 2 3 3 2
1
PROBLEM 4 : Find L1 2 2
s s 1 s 9
2
Solution :
F s
1
s2 s2 1 s2 9
Put s 2 u in above equation
1 1
s s 1 s2 9
2 2
u u 1u 9
.......... .......... 1
1 A B C
Consider
u u 1u 9 u u 1 u 9
1 A u 1u 9 B u u 9 C u u 1
u u 1u 9 u u 1u 9
1 A u 1u 9 B u u 9 C u u 1
1 1 1
1
9 8 72
u u 1u 9 u u 1 u 9
1 1 1
1
9 8 72
u u 1u 9 u u 1 u 9
1 1 1 1 1 1 1 1 1
L L L 2
9
u 8 u 1 72 u 3
1 1 1 sin 3t
t sin t .
9 8 72 3
1 1 1 1 sin 3t
L1 t sint .
s s 2
1 s 2
9 9 8 72 3
TASK
a2
4 Find L
1
3
s s a
2s 2 6s 5
5 Find L 1
s 1s 2 s 3
CONVOLUTION:
It is denoted by, f t * g t
i.e f t * g t f u g t u du.
t
CONVOLUTION THEOREM:
= e
0
st
t
0
f u g t u du dt
t
= e
st
f u g t u dudt---------------------(1)
0 0
Limits of u = 0 to t; t = 0 to
After changing the order of integration,
limits of u = 0 to ; t = u to
(1) becomes,
L f t * g t e
st
f u g t u dtdu
0 u
0
= f u e st g t u dt du
u
Let t u = v
dt = dv
when t = u, then v=0; t = ,then v =
L f t * g t f u e s u v g v dv du
0
= f u e su e sv g v dv du
0
t
0
0
= e st f u du e sv g v dv
0
f t dt e g t dt
st sv
= e
0 0
= L f t L g t
L f t * g t = F s G s
Hence, Convolution Theorem is proved
COROLLARY:
L f t * g t F s .G s
f t * g t L1 F s .L1 G s
L1 F s *L1 G s L1 F s .L1 G s
1 t
a0
sin a u t u sin a (u t u )du
s 1 1 a
s a s a s a
L1 L1 2 2
L 2 2
2 2 2
s s 1 1
NOTE: Proof :
1 cos t
s a
2) Using convolution theorem find L1
2
s
2 2
f t * g t g t * f t
sin t u du
0
1*sin t
s s 1 s s 1
L1 2 L .L 2
1 1
1 1
1
Solution:
s s 1
1) Using Convolution Theorem, find L1 2
1
Problems:
f t * g t g t * f t
NOTE:
1
1) Using Convolution Theorem find L1
s s 2
1
Solution:
1 1 1 1 1
L1 L .L
s s 1
2 s s 2 1
2a
1
t sin at
2a 0
1* sin t
sin t u du
t
1
1 cos t
1
L
s s 2
1
s
2) Using Convolution Theorem find L1
2
s 2
a 2
Solution:
s s 1 1
L1 L1 2 L 2
s a s a s a
2 2 2
2 2
s 1 1 a
L1 2 . L 2
s a s a
2 2
a
1
cos at * sin at
a
1
cos au.sin a t u du
t
a0
1 t
sin a u t u sin a u t u du
2a 0
1
t sin at
2a
3) Find1* et
Solution :
t
1* et 1.et u du
0
t
et u
1 0
et 1
4) Find t * et
Solution:
t
t * et ue t u du
0
t t
uet u et u
1 0 1 0
et t 1
d2y dy dy
3)Solve 2 4 5 y 5, y t 0, 2 whent 0;
dt dt dt
y 0 0; y1 0 2; y t 0, y1 t 0
Solution:
y11 t 4 y1 t 5 y t 5
L y11 t 4 L y1 t 5L y t 5L 1
s 2 L y (t ) sy 0 y1 0 4 sL y t y 0 5L y t 5L 1
1
s 2 L y (t ) s 0 2 4 sL y t y 0 5 L y t 5
s
5
L y (t ) s 2 4 s 5 2
s
5 2s
y t L 1
....................................................(1)
s s 2
4 s 5
5 2s 5 2s A B C
...............(2)
s s 2 4 s 5 s s 5 s 1 s s 5 s 1
5 2 s A s 5 s 1 Bs s 1 cs s 5 ...............(3)
1 7
We get A = -1,B = - ,C =
6 6
Substituting in 2 ,
5 2s 1 1 7
s s 5 s 1 s 6 s 5 6 s 1
5 2s 1 1 1 1 1 7 1 1
L1 L s 6 L s 5 6 L s 1
s s 5 s 1
7 1
et e 5t 1.....................................(4)
6 6
substituting (4) in (1)
7 1
y (t ) et e 5t 1
6 6
TASK:
dy
4 y 5 ydt e t , y 0 0
t
1) Solve
dt 0
dy
2 y ydt 2 cos t , y 0 1
t
2)Solve
dt 0
3)Solve y11 (t ) 3 y1 (t ) 2 y (t ) e 2 t
4)Solve y11 (t ) 2 y1 (t ) 3 y (t ) sin t , y (0) 0, y1 (0) 0
when t 0, y (t ) 0, y1 (t ) 0
1) Solve (𝑫𝟐 +𝟒)𝒚 = 𝒕 given that 𝒚(𝟎) = 𝒚’(𝟎) = 𝟎 and 𝑫 ≡ 𝒅/𝒅𝒕.
Soln:
Given 𝑦” 𝑡 + 4𝑦 𝑡 = 𝑡,
⇒𝐿 𝑦” 𝑡 + 4𝐿 𝑦 𝑡 = 𝐿 𝑡 ,
1
⇒ 𝑠 2 𝐿 𝑦 − 𝑠𝑦 0 − 𝑦’ 0 + 4𝐿 𝑦 = ,
𝑠2
1
Using initial conditions we obtain, 𝑠 2 + 4 𝐿 𝑦 = 2 ,
𝑠
2 2
⇒ 𝐿{𝑦} = 1/{𝑠 𝑠 + 4 ,
Taking inverse Laplace transform on both sides, we get
−1
1 1 −1 1 1 1
𝑦=𝐿 = 𝐿 − 2+4 = .
2 2
𝑠 𝑠 +4 4 𝑠 2 𝑠 𝑠𝑖𝑛2𝑡
4 𝑡−
2
2) Using Laplace transform method solve 𝑫 + 𝑫𝟐 𝒙 = 𝟐, if 𝒙 = 𝟑 and
𝒙’ = 𝟏 when 𝒕 = 𝟎.
Soln:
𝑥’(𝑡) + 𝑥”(𝑡) = 2,
Taking Laplace transformation on both sides we get, 𝐿 𝑥’ 𝑡
+ 𝐿 𝑥” 𝑡 = 2𝐿 1 ,
2
2
𝑠𝐿 𝑥 − 𝑥 0 + 𝑠 𝐿 𝑥 − 𝑠𝑥 0 − 𝑥’ 0 = ,
𝑠
2 2
Using boundary conditions we get, 𝑠𝐿 𝑥 − 3 + 𝑠 𝐿 𝑥 − 3𝑠 − 1 = ,
𝑠
2
2
𝑠 + 𝑠 𝐿 𝑥 = + 4 + 3𝑠,
𝑠
2
2
𝐿 𝑥 = 3𝑠 + 4𝑠 + 2 2 ,
𝑠 𝑠 +1
Using partial fraction technique we have,
1 2 2
𝐿 𝑥 = + + 2,
𝑠+1 𝑠 𝑠
Taking inverse Laplace transform, we get
𝑥 = 𝑒 −𝑡 + 2 + 2𝑡.
3) Solve 𝑫𝟐 + 𝟏 𝒚 = 𝟔𝒄𝒐𝒔𝟐𝒕, if 𝒚 = 𝟑, 𝑫𝒚 = 𝟏 when 𝒕 = 𝟎.
Soln:
𝑦” + 𝑦 = 6cos2𝑡,
Taking Laplace transform on both sides, we get 𝐿 𝑦” + 𝐿 𝑦 =
6𝐿 cos2𝑡 ,
2
6𝑠
𝑠 𝐿 𝑦 − 𝑠𝑦 0 − 𝑦’ 0 + 𝐿 𝑦 = 2 2
,
𝑠 +2
2 6𝑠
Using initial conditions, 𝑠 + 1 𝐿 𝑦 − 3𝑠 − 1 = 2 ,
𝑠 +4
𝐿{𝑦} = 3𝑠/(𝑠 2 +1) + 1/(𝑠 2 + 1) + 6𝑠/(𝑠 2 + 1)(𝑠 2 + 4),
Using partial fraction technique, we obtain 𝐿{𝑦} = 3𝑠/(𝑠 2 +1) +
1
1/(𝑠 + 1) + 2𝑠( 2 − 1/(𝑠 2 + 4)),
2
𝑠 +1
Taking inverse Laplace transform, we get
y=5cost+sint-2cos2t.
4) Find the general solution of 𝑫𝟐 + 𝒌𝟐 𝒚 = 𝟎 and verify
it.
Soln:
𝑦” + 𝑘 2 𝑦 = 0,
𝐿{𝑦”} + 𝑘 2 𝐿{𝑦} = 0,
𝑠 2 𝐿{𝑦} − 𝑠𝑦(0) − 𝑦’(0) + 𝑘 2 𝐿{𝑦} = 0,
(𝑠 2 + 𝑘 2 )𝐿{𝑦} − 𝐴𝑠 − 𝐵 = 0, where 𝑦(0) = 𝐴 and 𝑦’(0) = 𝐵,
𝐿{𝑦} = 𝐴𝑠 + 𝑏/(𝑠 2 +𝑘 2 ) = 𝐴 ∗ 𝑠/(𝑠 2 +𝑘 2 ) + 𝐵 ∗ 1/(𝑠 2 +𝑘 2 )
Taking inverse Laplace transformation, we get y=Acoskt+Csinkt,
where C=B/k.
Differentiating (2) wrt t and substituiting in (1) satisfies (1). Hence it
is a solution.
5) Solve (𝑫𝟐 + 𝑫) 𝒙 = 𝟐, when 𝒙 (𝟎) = 𝟑, 𝒙′ (𝟎) = 𝟏.
Soln:
𝑥” + 𝑥’ = 2,
𝐿 𝑥” + 𝐿 𝑥’ = 2𝐿 1 ,
1
𝑠2𝐿 𝑥 − 𝑠𝑥 0 − 𝑥’ 0 + 𝑠𝐿 𝑥 − 𝑥 0 = 2 ∗ ,
𝑠
2
Using initial condition, we get 𝑠2
+ 𝑠 𝐿 𝑥 − 3𝑠 − 1 − 3 = ,
𝑠
2
2
𝑠 + 𝑠 𝐿 𝑥 = 3𝑠 + 4 + ,
𝑠
Using partial fractions, we get
1 2 2
𝐿 𝑥 = +1+ + 2,
𝑠 𝑠 𝑠
Taking inverse Laplace transform ,
𝑥 = 𝑒 −1 + 2 + 2𝑡.
6) Solve 𝑫𝟐 + 𝟒𝑫 + 𝟖 𝒚 = 𝟎, 𝒚 𝟎 = 𝟐, 𝒚′ 𝟎 = 𝟐.
Soln:
𝑦” + 4𝑦’ + 8𝑦 = 0
Taking Laplace transformation on both side we get, 𝐿{𝑦”} + 4𝐿{𝑦’} + 8𝐿{𝑦} =
0,
𝑠 2 𝐿{𝑦} − 𝑠𝑦(0) − 𝑦’(0) + 4[𝑠𝐿{𝑦} − 𝑦(0)] + 8𝐿{𝑦} = 0,
Using initial value condition, we get
(𝑠 2 + 4𝑠 + 8)𝐿{𝑦} − 2𝑠 − 2 − 8 = 0,
𝐿 𝑦 = (2𝑠 + 10)/(𝑠 2 + 4𝑠 + 8),
𝑦 = 𝐿^ − 1{2(𝑠 + 2) + 6/ 𝑠 + 2 2 + 4,
= 𝑒 −2𝑡 𝐿−1 {2𝑠 + 6/𝑠 2 + 4},
−2𝑡 −1 2 2 −1 1
= 𝑒 [2𝐿 {𝑠/𝑠 + 2 } + 6𝐿 { 2 2 }],
(𝑠 +2 )
= 𝑒 −2𝑡 (2cos2𝑡 + 3sin2𝑡).